2001
DOI: 10.1007/s004020000193
|View full text |Cite
|
Sign up to set email alerts
|

Correction of kyphotic deformity before and after transection of the anterior longitudinal ligament - a cadaver study

Abstract: With a custom-made measuring unit, two separate experiments, involving six and five cadaveric torsos with intact rib cages and sternums, respectively, were carried out to determine the effect of the transection of the anterior longitudinal ligament with and without osteodiscectomy and its influence on the thoracic kyphosis. The open or thoracoscopically assisted anterior release, as part of the operative treatment of scoliosis or kyphosis, usually consists of a transection of the anterior longitudinal ligament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 16 publications
0
15
0
1
Order By: Relevance
“…A cadaver study reported that anterior longitudinal ligament transection at T3–T7 resulted in a Cobb angle reduction of 16° [44]. This association was strengthened in a cross-sectional study of 1172 older adults in the Health, Ageing and Body composition cohort.…”
Section: Decreased Mobility and Age-related Hyperkyphosismentioning
confidence: 99%
“…A cadaver study reported that anterior longitudinal ligament transection at T3–T7 resulted in a Cobb angle reduction of 16° [44]. This association was strengthened in a cross-sectional study of 1172 older adults in the Health, Ageing and Body composition cohort.…”
Section: Decreased Mobility and Age-related Hyperkyphosismentioning
confidence: 99%
“…Cadaver studies suggest that calcification and ossification of the anterior longitudinal ligament in the thoracic region might contribute to increased Cobb’s angle of kyphosis 4. Furthermore, shorter pectoral and hip flexor muscles are linked to severe hyperkyphosis, although it is not known whether the short muscles pull the shoulders and hips anteriorly, or whether the kyphotic posture results in shorter anterior musculature.…”
Section: Risk Factorsmentioning
confidence: 99%
“…However, many elderly people have abnormal posture, represented by hyperkyphosis, without pain or a history of such fractures. Recent studies demonstrates that many older adults who are mostly affected by hyperkyphosis do not have vertebral fractures [3], and other postulated causes of hyperkyphosis include postural changes [4], degenerative disc disease [5], muscular weakness [6,7], ligamentous degeneration [8], and genetic predisposition [9]. Such abnormal posture may be associated with multiple adverse health outcomes, including gait disorder, becoming bedridden.…”
Section: Introductionmentioning
confidence: 99%